2010
DOI: 10.1186/1471-2229-10-198
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic disruptions in seuss cyp85A2 double mutants reveal a role for brassinolide synthesis during gynoecium and ovule development

Abstract: BackgroundThe Arabidopsis SEUSS (SEU) gene encodes a transcriptional adaptor protein that is required for a diverse set of developmental events, including floral organ identity specification, as well as gynoecium, ovule and embryo development. In order to better understand the molecular mechanisms of SEUSS action we undertook a genetic modifier screen to identify seuss-modifier (sum) mutations.ResultsScreening of M2 lines representing approximately 5,000 M1 individuals identified mutations that enhance the seu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
(35 reference statements)
0
36
0
1
Order By: Relevance
“…Mutation in the BR biosynthetic enzyme CYP85A2 enhances the phenotype of the Arabidopsis mutant seuss, which is defective in ovule and gynoecial development (Nole-Wilson et al, 2010). In addition, the CYP85A1 gene is expressed in the developing female gametophyte and cyp85a1 mutants exhibit a semisterile phenotype (Pé rez-Españ a et al, 2011).…”
Section: Male and Female Fertilitymentioning
confidence: 99%
“…Mutation in the BR biosynthetic enzyme CYP85A2 enhances the phenotype of the Arabidopsis mutant seuss, which is defective in ovule and gynoecial development (Nole-Wilson et al, 2010). In addition, the CYP85A1 gene is expressed in the developing female gametophyte and cyp85a1 mutants exhibit a semisterile phenotype (Pé rez-Españ a et al, 2011).…”
Section: Male and Female Fertilitymentioning
confidence: 99%
“…Moreover, the same study showed by ChIP analysis that BES1 directly binds to the promoters of many of these genes, indicating there is a direct BR response on the expression of genes essential for anther and pollen development (Ye et al, 2010). A novel role for BRs in gynoecium and ovule development has also been uncovered recently through genetic screens that identified a BR biosynthetic enzyme as a suppressor of mutations in the Arabidopsis SEUSS gene, encoding a transcriptional adaptor protein involved in floral organ identity and the development of the carpel margin meristem (Nole-Wilson et al, 2010).…”
Section: Reproductive Developmentmentioning
confidence: 99%
“…Bars with different letters are significantly different at P , 0.05, ANOVA. Bao et al, 2010;Nole-Wilson et al, 2010;Lee et al, 2014), we initiated studies to determine the potential role of SEU in root development. Two seu mutants, seu-3 and seu-4, which were previously identified in searches for floral organ patterning mutants (Pfluger and Zambryski, 2004), were utilized for these studies.…”
Section: Seu Represses MC Formation In the Root Endodermismentioning
confidence: 99%
“…nA, No antibody; Ab, GFP antibody. Azhakanandam et al, 2008;Bao et al, 2010;Nole-Wilson et al, 2010;Lee et al, 2014). Interestingly, although SEU does not appear to possess a recognizable DNA-binding motif, it was shown by chromatin immunoprecipitation (ChIP) to associate with cis-regulatory elements located in the second intron of the floral homeotic gene AGAMOUS (AG; Sridhar et al, 2006) and with cisregulatory elements of miR172 genes (Grigorova et al, 2011).…”
mentioning
confidence: 99%